2011
DOI: 10.1186/1472-6750-11-95
|View full text |Cite
|
Sign up to set email alerts
|

Synergizing metabolic flux analysis and nucleotide sugar metabolism to understand the control of glycosylation of recombinant protein in CHO cells

Abstract: BackgroundThe glycosylation of recombinant proteins can be altered by a range of parameters including cellular metabolism, metabolic flux and the efficiency of the glycosylation process. We present an experimental set-up that allows determination of these key processes associated with the control of N-linked glycosylation of recombinant proteins.ResultsChinese hamster ovary cells (CHO) were cultivated in shake flasks at 0 mM glutamine and displayed a reduced growth rate, glucose metabolism and a slower decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 25 publications
6
50
1
1
Order By: Relevance
“…7). Burleigh et al reported that lack of glutamine in the medium coupled with reduced glycolysis causes a reduction in the sialylation and branching of N-glycans in recombinant glycoproteins (38). A significant difference between our finding and this finding is that the Min6 insulinoma cell line contained a high level of nucleotide sugars.…”
Section: Quantitative Analysis Of N-glycans and Secreted Hyaluroniccontrasting
confidence: 79%
“…7). Burleigh et al reported that lack of glutamine in the medium coupled with reduced glycolysis causes a reduction in the sialylation and branching of N-glycans in recombinant glycoproteins (38). A significant difference between our finding and this finding is that the Min6 insulinoma cell line contained a high level of nucleotide sugars.…”
Section: Quantitative Analysis Of N-glycans and Secreted Hyaluroniccontrasting
confidence: 79%
“…The same authors report no significant glycan differences in continuous culture between two steady states by decreasing the Gln concentration from 8 to 0 mM. Nonetheless, between additional steady states (steady state 3: 8 mM Gln, steady state 4: 0 mM Gln) a significant glycan species distribution occurred thus showing the impact of the metabolic flux on glycosylation 117 . Following the addition of sucrose, which led to higher levels of high mannose glycans (cf.…”
Section: Fucosylationmentioning
confidence: 90%
“…In contrast to human IgG, sialic acids are attached to the terminal galactose residues of antibodies expressed in CHO cells via an α-2,3 linkage exclusively 68 . It was reported that by reducing glutamine concentrations to 0 mM in CHO-K1 batch and perfusion cultures, sialylation was inhibited, thus leading to more abundant neutral N-linked glycans 117 . Dimethyl sulfoxide (DMSO) from 1 to 8% (v/v) reduced sialylation but at the same time negatively impacted cell proliferation 139 .…”
Section: Sialylationmentioning
confidence: 99%
“…For this reason, it is generally desirable to select a production cell line that produces IgG with low HM glycosylation. However, since glycosylation is sensitive to small, potentially unforeseen changes in cell culture and manufacturing (Burleigh et al, 2011;Chee Furng Wong et al, 2005;Crowell et al, 2007;Hossler et al, 2009;Li et al, 2010;Muthing et al, 2003;Walsh and Jefferis, 2006), it would be advantageous to predict the potential amount of IgG HM glycosylation either before or during the development of the manufacturing process. Therefore, understanding the causes for HM glycosylation in CHO cells is needed.…”
Section: Introductionmentioning
confidence: 99%